INTRODUKSI PEMBUATAN WASTAFEL PORTABEL SISTEM INJAK UNTUK PENCEGAHAN COVID-19 DI NAGARI TARANTANG KABUPATEN LIMAPULUH KOTA - Nelvia Iryani; Nur Ari Sufiawan; Faisal Ali Ahmad; Alfikri Alfikri (Jurnal Hilirisasi IPTEKS, 2021)
Nagari Tarantang is one of the villages located in Harau District, Limapuluh Kota Regency. Farming and gardening are the main livelihoods of the people. In addition, the green nature that surrounds the valleys and cliffs makes Nagari Tarantang one of the famous tourist destinations, namely the Harau Valley Tourism Area. This activity aims to help Nagari Tarantang in breaking the chain of the spread of Covid-19, especially in public areas such as the Harau Valley tourist area, mosques, and Nagari government offices by socializing the use of a portable sink with a tread system to the public and tourists visiting the area. In order to achieve this goal, the method used in this activity is to conduct socialization about the importance of using a tread system portable sink to the people of Nagari Tarantang. The implementation of this activity is carried out intensively, directed, and gradually. The stages and methods used are 1. Equipment Fulfillment Stage, 2. Manufacturing Stage, and 3. Delivery Stage. The results of the activities obtained by all these series of activities went well. All counseling participants received knowledge about the importance of washing hands to break the chain of the spread of the Covid-19 virus in Nagari Tarantang. In addition, he has helped build several portable sinks with a tread system to be placed in public areas such as the Harau Valley tourist area, mosques, and the office of Walinagari Tarantang. With the completion of this activity, it is hoped that the community and visitors to the Harau Valley tourist attraction can use a portable sink with the tread system to wash their hands before and after entering the Harau Valley Tourism Area as well as public areas in Nagari Tarantang such as the Harau Valley tourist area, mosques, and the office of Walinagari Tarantang.